คิดนอกกรอบ: การพัฒนาครู: แก้ปัญหาให้ตรงจุด - สุดรุ่ง, จุไรรัตน์; ถนอมพงษ์ชาติ, ผัสสพรรณ (Journal of Education Studies, Chulalongkorn University, 2018)
Abstract To develop teachers to be effective in teaching needs to know the basics of the teacher to see the root of the problems that arise. It is evident that teachers have also many other tasks besides teaching. Based on the research findings and teacher education data from other Asian countries, for effective teaching and learning teachers should engage in the teaching task only. Spending a lot of budget on teacher development in various ways is not effective at all if the teacher does not have time to teach heartily. Placing the teacher back in the classroom, then developing, supervising, and monitoring them is the corrective solution.